One and The Same Route: Two Outstanding Electrodynamics - Accioly, Antonio Jose [UNESP]; Mukai, Hatsumi (Sociedade Brasileira de Física, 1998)
We show that the same route that leads to Maxwell's electrodynamics leads also to Podolsky's electrodynamics, provided we start from Podolsky's electrostatic force law instead of the usual Coulomb's law.